Characterization of some satellite DNA families in Deschampsia antarctica (Poaceae) - González, María Laura; Chiapella, Jorge Oscar; Urdampilleta, Juan Domingo (Polar Biology)
Deschampsia antactica E. Desv. is one of the only two native vascular plants of Antarctica, having a disjunct distribution with South America. Its presence in different environmental conditions turn it into an interesting evolution model, particularly for genomic evolutionary studies. The repetitive DNA is a genome component, that cause important changes in genome size and chromosome organization, and therefore its variation is very important in group?s delimitation. Some tandem repetitive DNA sequences, known as satellite DNA (satDNAs) are shared between many groups of Poaceae (e.g. of these are the CON1, CON2, COM1 and COM2 sequences) highlighting its evolutionary component. This study aims to identify, classify and characterize repetitive elements in the D. antarctica genome by clustering analysis of genome sequences, focusing on the CON1, CON2, COM1 and COM2. Repetitive DNA represented about 73.3% of the D. antarctica genome. All studied populations presented loci for the studied satDNAs but the distribution pattern showed differences than seem to be related to the geographic distribution. The analysis of CON/COM sequences in D. antarctica contributes with the understanding of these elements in Poaceae genomes and highlights the importance of changes in chromosome organization of repetitive DNA in populations with fragmented geographical distribution. The distribution of such chromosome changes may both reflect the process of colonization of D. antarctica in Antarctica and explain some evolutionary processes of differentiation in Deschampsia species complex in the Patagonia, still unresolved with other DNA sequences. Fil: González, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Chiapella, Jorge Oscar. Consejo Nacional de Investigaciones ...